Membangun Aplikasi Web Pencatat Iuran Kas Kelas Mingguan Dengan Metode Waterfall Untuk Meningkatkan Efisiensi Dan Transparansi Finansial Siswa Di SMKS Cakra Nusantara Depok - Mifdzal Azriel; Achmad Raihan; Ahmad Yusuf Syaifullah; Heni Setiawati; Henry Mufid; Muhammad Lutfi Syabriyan; Muhammad Rofi Baihaqi; Mutia Salsa Rizkyta; Shanika Karin; Hibatullah Dzaky Ikram Hakim; Tri Prasetyo (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Class cash dues management in schools is still largely done manually using notebooks or simple record keeping, leading to various problems such as delays in recording, difficulties in data recapitulation, low transparency, and a high risk of recording errors and data loss. This Community Service activity aims to implement a web application for recording weekly class cash dues at SMK Cakra Nusantara Depok to improve the efficiency and transparency of class financial administration. The implementation method involved system design, application development using the Waterfall method, and direct training and mentoring for students. The results of the activity demonstrated that the web application facilitated faster, neater, and more accurate cash transaction recording and increased transparency in class cash management.